Axiological and Praxeological Dimensions of Marketing Communication Effectiveness – A Conceptual Framework - Kolwas Szymon; Domański Jarosław (Foundations of Management, 2023)
Analyzed from the sender’s perspective, marketing communications aim to engage audiences and create benefit-oriented relationships. In order to adequately assess the reciprocal efforts of the sender and receiver of the communication process, one cannot limit oneself to its purely economic analysis, but should pay attention to its broader praxeological context – take into account factors such as efficiency, effectiveness, and expediency. It is also crucial to evaluate parameters beyond the purely usability characteristics of communication practices used in the marketing aspect. Their ethical evaluation from current and potential customers, the social environment, and other stakeholders poses significant challenges for communicators but should also spur potentially beneficial transformations – toward a new view of socially engaged marketing and the ethical dimension of marketing. The purpose of this inquiry is to identify a conceptual framework for measuring the efficiency of marketing communications based on axiological and praxeological dimensions. Five research hypotheses were formulated, which can be verified in the future research.